Home security sensor system using atmel AVR microcontroller - Lim, Boon Hoi (Universiti Malaysia Sarawak, UNIMAS, 2006)
The AVR Flash Microcontroller based Home Security Sensor System is an automated home alarm system with built-in centralized security monitoring system prototyped using the Atmel STK500 starter kit. The system is able to monitor the house by displaying the information of the current condition of the house and trigger the alarm when the house is being broken in. The development of this home security sensor system involves both hardware and software components. The hardware interface is used to connect all the sensors in the model of the house together with a display panel. The hardware circuit design is built on the AT90S8515 microcontroller. The software program developed is used to control all the functions of the system and it is developed using the AVR studio. The AVR studio is a specific tool for Atmel based assembly program development and debugging. The Home Security Sensor System can be further extended to become more comprehensive in the future.